2019
DOI: 10.1007/s10639-019-09995-z
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives for effective integration of e-learning tools in university mathematics instruction for developing countries

Abstract: This paper analyses student views on an e-learning intervention that incorporated a content development tool and computer algebra systems, aimed at improving performance and applicability of mathematics knowledge. The study deliberately relied on open source tools, with high usability both online and offline, that can be customized to address the peculiarities of mathematics instruction in developing countries. Repeated ANOVA and logistic regression were among the statistical methods used to analyze the data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…When the number-counting habits are approved by the conscious mind, they are stored in the subconscious mind (Murphy 2008) so that individuals are able to count even if they are not concentrating on the counting. All mathematics sections need an understanding of number counting and other parts of algebra as their first requirement/prerequisite before they are learnt (Akugizibwe and Ahn 2019;Bansilal 2015). Decolonisation of mathematics content should therefore start with algebra, in order to produce a platform for other sections with their aims.…”
Section: Conclusion and Education Implicationsmentioning
confidence: 99%
“…When the number-counting habits are approved by the conscious mind, they are stored in the subconscious mind (Murphy 2008) so that individuals are able to count even if they are not concentrating on the counting. All mathematics sections need an understanding of number counting and other parts of algebra as their first requirement/prerequisite before they are learnt (Akugizibwe and Ahn 2019;Bansilal 2015). Decolonisation of mathematics content should therefore start with algebra, in order to produce a platform for other sections with their aims.…”
Section: Conclusion and Education Implicationsmentioning
confidence: 99%
“…This positive effect of e-education on the overall performance is in line with Diab & Elgahsh's findings who reported that e-education has led to the enhancement of the overall students' performance during the Covid-19 pandemic (Diab & Elgahsh, 2020). Even before the pandemic, several studies have reported better performance using e-education methods compared to conventional methods (Akugizibwe & Ahn, 2020;Dodiya et al, 2019;Lumadi, 2013). However, a large meta-analysis study in 2019 found the effect of the flipped classroom to be moderate on students' performance and recommended further research to explore it (Strelan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the inception of the internet over a few decades back, the overall influence of internet technology on developing countries' economies has yet to be defined, and no more experience has been gained [13]. Level of Experience in the internet and computers in developing countries different from developed countries [13], [14], [117], [118], [109], [119], [120], [121], [110].…”
Section: Experience In the Internet And Computermentioning
confidence: 99%